Delničarski direktivi I in II ter ZGD-1 - Kocbek, Marijan (Podjetje in delo, 2020)
The paper examines the regulation of shareholder rights within the EU. The first Shareholder Rights Directive was adopted by the EU in 2007 and implemented in Slovenia with the amendment to the Companies Act - ZGD-1C. As a response to the financial crisis, in order to prevent or mitigate future crises, the first Directive was amended after 10 years by a directive to encourage long-term shareholder participation. Slovenia will implement the Shareholder Rights Directive II with the amendment to the Companies Act - ZGD-1K. As the discussions on the implementation of the Directive are currently underway in the legislative procedure, the author discusses the current legal regulation of the corporate law institutes of the Companies Act (ZGD-1) that are related to the Directive.
Keywords: glasovalna pravica; identification of shareholders; identifikacija delničarjev; nagrajevanje uprave; povezane osebe; pravice delničarjev; related parties; remuneration of the management board; shareholder rights; voting right